INTEGRATION OF MANAGEMENT OF RELIGIOUS ACTIVITIES AND LITERACY TO IMPROVE THE QUALITY OF RELIGIOUS CHARACTER - Muhammad Fauzul Fikri; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The digital transformation in the contemporary era demands that madrasas adapt their curricula to ensure educational relevance while simultaneously addressing the challenges of moral disruption and the erosion of students' spiritual values. This study aims to formulate a model for integrating religious activities with literacy in madrasahs and to analyze the implementation of the Planning, Organizing, Actuating, and Controlling (POAC) management functions in enhancing the quality of students' religious character. Employing a library research method with a qualitative approach and content analysis, this study examines various reputable literatures to construct a comprehensive conceptual model. The results indicate that policy fragmentation between religious programs and literacy can be overcome through a Total Quality Management (TQM) approach, which unifies spiritual substance with digital literacy skills into a cohesive learning ecosystem. The disciplined implementation of POAC, ranging from vision alignment and cross-role collaboration to the use of a dual monitoring system (physical logs and digital portfolios), has proven effective in transforming religious routines into a holistic educational ecosystem. This integration model positions religious values as the primary filter in digital literacy management, thereby producing graduates who are not only excelling in ritual obedience but also possess critical, adaptive, and high-integrity literacy amidst the challenges of the times.